Environment-friendly carbon-reduction type high-strength and high-toughness concrete and preparation method thereof
By using carbon dioxide, gold tailings sand and high alumina cement in high tough concrete to prepare aragonite whiskers and hydrated calcium carbonate in high tough concrete, replacing PVA fiber, the high cost and carbon emission problems of high tough concrete are solved, and high strength is achieved. High toughness and low carbon emission effects.
Patent Information
- Application Number
- CN202411301193.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-18
- Publication Date
- 2025-02-18
AI Technical Summary
The existing high-toughness concrete materials account for a small proportion of high-cost PVA fibers and cement, resulting in high costs and low compressive strength, which limits their application in engineering construction and also faces the challenges of carbon emission control.
Environmentally friendly carbon-reducing high-strength and high-tough concrete are prepared by using carbon dioxide, gold tailings sand and high-aluminum cement, instead of PVA fiber.
It has achieved high strength and high toughness, compressive strength reaches more than 35MPa, and the ultimate strain exceeds 3%. At the same time, carbon emissions are reduced, material costs are reduced, and high toughness concrete is promoted to the widespread application of high toughness concrete in engineering construction.
Smart Images

Figure CN119462027A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of concrete material preparation, and in particular relates to an environmentally friendly, carbon-reducing, high-strength, high-toughness concrete and a preparation method thereof. Background Art
[0002] Cement concrete pavement has become the most common and widely used building material in my country due to its advantages such as high strength, good stability and low cost. With the continuous advancement of urban construction, the quality requirements of construction materials in engineering construction are increasing. However, the toughness of ordinary concrete is poor, and the tensile strain performance does not exceed 0.01%. Therefore, when concrete beams, slabs and other components are subjected to bending and tensile loads, they are easily damaged, resulting in a reduction in their service life. Based on this, some scholars have developed fiber-doped high-toughness concrete materials to meet the design requirements of components subjected to bending and tensile loads.
[0003] At present, high-toughness concrete is often mixed with PVA fibers and a large proportion of fly ash is used to replace cement to reduce the initial crack strength of concrete when subjected to bending and tension, so that the concrete cracking stress is less than the tensile capacity of the fiber, thereby achieving multi-crack cracking and high toughness of high-toughness concrete. However, the cost of PVA fibers is extremely high, and because the proportion of cement is small, the cost of high-toughness concrete is high and the compressive strength is low, which limits the scope of engineering use of high-toughness concrete.
[0004] On the other hand, controlling carbon emissions has become a challenge faced by my country and the world. Storing carbon dioxide in cement-based materials has been proven to be a promising solution for carbon capture, storage and utilization. Therefore, preparing a building material that can solidify and store carbon dioxide is beneficial to my country's environmental protection and economic development. Summary of the invention
[0005] The purpose of an embodiment of the present invention is to provide an environmentally friendly, carbon-reducing high-strength and high-toughness concrete and a preparation method thereof, which uses carbon dioxide, gold tailings and high-alumina cement to prepare aragonite whiskers and hydrated calcium aluminate to replace PVA fibers to prepare high-strength and high-toughness concrete, which can effectively reduce carbon emissions, thereby solving at least one technical problem involved in the background technology.
[0006] In order to solve the above-mentioned technical problems, the present invention is achieved as follows:
[0007] The embodiment of the present invention provides an environmentally friendly, carbon-reducing, high-strength and high-toughness concrete, which includes, by weight, 265 to 310 parts of cement, 265 to 930 parts of fly ash, 50 to 250 parts of silica fume, 250 parts of gold tailings sand, 20 to 150 parts of water reducer, 10 to 20 parts of thickener, 30 to 50 parts of a mixture of hydrated calcium aluminate and strip aragonite whiskers, and 115 to 500 parts of water, wherein the water-cement ratio is 0.2 to 0.35.
[0008] Optionally, the water reducing agent is selected from polycarboxylic acid-based high-efficiency water reducing agent, and the water reduction rate is greater than 20%.
[0009] Optionally, the thickener is a hydroxypropyl cellulose thickener with a viscosity between 3500 and 4000 cpa·s.
[0010] Optionally, the mixture of hydrated calcium aluminate and long rod-shaped aragonite is prepared by the following method:
[0011] The gold tailings are placed in a saturated solution of calcium hydroxide to provide crystallization sites for aragonite whiskers;
[0012] Add magnesium chloride powder and high alumina cement and stir evenly until all are dissolved to form a mixed suspension of magnesium hydroxide and high alumina cement;
[0013] The mixed suspension of magnesium hydroxide and high-alumina cement is heated to maintain the temperature of 80°C, and carbon dioxide gas is introduced. Under the action of magnesium ions, calcium ions react with carbon dioxide to form calcium carbonate precipitates and magnesium carbonate precipitates. Calcium carbonate uses gold tailings as nucleation points to form strip-shaped aragonite whiskers. The calcium carbonate component in the gold tailings reacts with high-alumina cement to form needle-shaped hydrated calcium aluminate. After a certain period of time, the mixture of strip-shaped aragonite whiskers and hydrated calcium aluminate is taken out.
[0014] Optionally, the mixture of strip-shaped aragonite whiskers and hydrated calcium aluminate carbonate is taken out after 5 hours.
[0015] Optionally, in the mixture of hydrated calcium aluminate carbonate and strip-shaped aragonite whiskers, the ratio of hydrated calcium aluminate carbonate to strip-shaped aragonite whiskers is 0.25-4.
[0016] The present invention also provides a method for preparing the environmentally friendly carbon-reducing high-strength and high-toughness concrete, comprising the following steps:
[0017] Step 1: provide 265-310 parts of cement, 265-930 parts of fly ash, 50-250 parts of silica fume, 250 parts of gold tailings, 20-150 parts of water reducer, 10-20 parts of thickener, 30-50 parts of a mixture of hydrated calcium aluminate and long rod-shaped aragonite, and 115-500 parts of water, by weight;
[0018] Step 2: Add cement, fly ash, silica fume, gold tailings sand and thickener into a reactor and stir evenly, then add water and water reducing agent and continue stirring to form a uniform mixture;
[0019] Step three, adding hydrated calcium aluminate and strip-shaped aragonite whisker mixture to the mixture, stirring evenly, placing it in a high humidity and normal temperature environment, and obtaining an environmentally friendly, carbon-reducing, high-strength and high-toughness concrete material after solidification.
[0020] Optionally, in step 2, the stirring time in the reactor is 3 minutes; the stirring time is continued for 5 minutes.
[0021] Optionally, in step three, the stirring time is 10 minutes.
[0022] Compared with the prior art, the present invention has the following beneficial effects:
[0023] (1) The environmentally friendly, carbon-reducing high-strength and high-toughness concrete provided by the present invention has a compressive strength of more than 35 MPa and an ultimate strain of more than 3%, which meets the design requirements of components subjected to high-strength axial compression loads and bending and tension loads in engineering construction.
[0024] (2) The present invention uses carbon dioxide to prepare strip-shaped aragonite whiskers, which replace PVA fibers to prepare high-strength and high-toughness concrete. On the one hand, this reduces the preparation cost of high-strength and high-toughness concrete and promotes the practical application of high-toughness concrete in engineering projects. On the other hand, it can solidify carbon dioxide and reduce the carbon content in nature, which is in line with my country's environmental protection policy.
[0025] (3) While preparing long rod-shaped aragonite whiskers, hydrated calcium aluminate is generated by the reaction of gold tailings and high-alumina cement, which can obtain a higher strength PVA fiber substitute. Both aragonite whiskers and hydrated calcium aluminate can play a bridging effect when concrete cracks, thereby improving the toughness of concrete. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the following briefly introduces the drawings required for describing the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative work, among which:
[0027] Figure 1 The present invention provides a preparation flow chart of the method for preparing the environmentally friendly, carbon-reducing high-strength and high-toughness concrete. DETAILED DESCRIPTION
[0028] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0029] The embodiment of the present invention provides an environmentally friendly, carbon-reducing, high-strength and high-toughness concrete, which includes, by weight, 265 to 310 parts of cement, 265 to 930 parts of fly ash, 50 to 250 parts of silica fume, 250 parts of gold tailings sand, 20 to 150 parts of water reducer, 10 to 20 parts of thickener, 30 to 50 parts of a mixture of hydrated calcium aluminate and strip aragonite whiskers, and 115 to 500 parts of water, wherein the water-cement ratio is 0.2 to 0.35.
[0030] The water reducing agent is selected from polycarboxylic acid series high efficiency water reducing agent, and the water reducing rate is greater than 20%.
[0031] The thickener is hydroxypropyl cellulose, and the viscosity is between 3500 and 4000 cpa·s.
[0032] Specifically, the mixture of hydrated calcium aluminate and long rod-shaped aragonite is prepared by the following method:
[0033] The gold tailings are placed in a saturated solution of calcium hydroxide to provide crystallization sites for aragonite whiskers;
[0034] Add magnesium chloride powder and high alumina cement and stir evenly until all are dissolved. The magnesium ion concentration can be controlled at 0.1 Mol / L, 0.2 Mol / L, 0.4 Mol / L, and 0.8 Mol / L to form a mixed suspension of magnesium hydroxide and high alumina cement;
[0035] The mixed suspension of magnesium hydroxide and high-alumina cement is heated to 80°C using an alcohol lamp or an induction cooker, and carbon dioxide gas is introduced. Under the action of magnesium ions, calcium ions react with carbon dioxide to form calcium carbonate precipitates and magnesium carbonate precipitates. Calcium carbonate uses gold tailings as nucleation points to form strip-shaped aragonite whiskers. The calcium carbonate component in the gold tailings reacts with high-alumina cement to form needle-shaped hydrated calcium aluminate. After 5 hours, the strip-shaped aragonite whiskers and the hydrated calcium aluminate are taken out.
[0036] In the present invention, the ratio of hydrated calcium aluminate carbonate to strip-shaped aragonite whiskers is 1:0.25-4.
[0037] See also Figure 1 As shown, the present invention also provides a method for preparing the environmentally friendly carbon-reducing high-strength and high-toughness concrete, comprising the following steps:
[0038] Step 1: provide 265-310 parts of cement, 265-930 parts of fly ash, 50-250 parts of silica fume, 250 parts of gold tailings, 20-150 parts of water reducer, 10-20 parts of thickener, 30-50 parts of a mixture of hydrated calcium aluminate and long rod-shaped aragonite, and 115-500 parts of water, by weight;
[0039] Step 2: Add cement, fly ash, silica fume, gold tailings and thickener into the reactor and stir for 3 minutes until the mixture is evenly mixed, then add water and water reducing agent and continue stirring for 5 minutes until the mixture is evenly mixed to form a uniform mixture;
[0040] Step three, add a mixture of hydrated calcium aluminate and strip aragonite whiskers (the ratio of the two is 1:0.25-4) to the mixture, stir for 10 minutes until the mixture is evenly mixed, place it in a high humidity and normal temperature environment, and after solidification, obtain an environmentally friendly, carbon-reducing, high-strength and high-toughness concrete material.
[0041] The preparation method of the environmentally friendly, carbon-reducing high-strength and high-toughness concrete provided by the present invention is described in detail below with specific embodiments and comparative examples.
[0042] Example 1
[0043] Embodiment 1 provides a method for preparing an environmentally friendly, carbon-reducing, high-strength, high-toughness concrete, comprising the following steps:
[0044] (1) Weigh 265 parts of cement, 265 parts of fly ash, 250 parts of silica fume, 250 parts of gold tailings sand, and 10 parts of thickener in a reactor and stir for 3 minutes to obtain a dry mix;
[0045] (2) Slowly add 20 parts of water reducer into 115 parts of water and stir for 5 minutes to obtain a uniform mixture;
[0046] (3) Weigh 30 parts of a mixture of hydrated calcium aluminate and strip-shaped aragonite whiskers (the ratio of the two is 1:1), put it into the mixture and stir for 10 minutes until it is uniform, then place it in a high humidity and normal temperature environment, and after solidification, obtain an environmentally friendly, carbon-reducing, high-strength and high-toughness concrete material.
[0047] Example 2
[0048] Embodiment 2 provides a method for preparing an environmentally friendly, carbon-reducing, high-strength, high-toughness concrete, comprising the following steps:
[0049] (1) Weigh 265 parts of cement, 265 parts of fly ash, 250 parts of silica fume, 250 parts of gold tailings sand, and 10 parts of thickener in a reactor and stir for 3 minutes to obtain a dry mix;
[0050] (2) Slowly add 20 parts of water reducer into 115 parts of water and stir for 5 minutes to obtain a uniform mixture;
[0051] (3) Weigh 40 parts of a mixture of aragonite whiskers and hydrated calcium aluminate (in a ratio of 1:1), put them into the mixture and stir for 10 minutes until they are uniform, then place them in a high humidity and room temperature environment, and after solidification, obtain an environmentally friendly, carbon-reducing, high-strength, and high-toughness concrete material.
[0052] Example 3
[0053] Embodiment 3 provides a method for preparing an environmentally friendly, carbon-reducing, high-strength, high-toughness concrete, comprising the following steps:
[0054] (1) Weigh 265 parts of cement, 265 parts of fly ash, 250 parts of silica fume, 250 parts of gold tailings sand, and 10 parts of thickener in a reactor and stir for 3 minutes to obtain a dry mix;
[0055] (2) Slowly add 20 parts of water reducer into 115 parts of water and stir for 5 minutes to obtain a uniform mixture;
[0056] (3) Weigh 50 parts of a mixture of aragonite whiskers and hydrated calcium aluminate (in a ratio of 1:1), put them into the mixture and stir for 10 minutes until they are uniform, then place them in a high humidity and room temperature environment, and after solidification, obtain an environmentally friendly, carbon-reducing, high-strength, and high-toughness concrete material.
[0057] Comparative Example 1
[0058] Comparative Example 1 provides a method for preparing concrete, comprising the following steps:
[0059] (1) Weigh 265 parts of cement, 265 parts of fly ash, 250 parts of silica fume, 250 parts of gold tailings sand, and 10 parts of thickener in a reactor and stir for 3 minutes to obtain a dry mix;
[0060] (2) Slowly add 20 parts of water reducer into 115 parts of water and stir for 5 minutes to obtain a uniform mixture;
[0061] (3) Weigh 50 parts of PVA fibers and add them to the mixture, stirring for 10 minutes until the mixture is uniform, thereby obtaining concrete.
[0062] The concrete materials prepared in Examples 1 to 3 and Comparative Example 1 were poured into a mold, demolded after curing at room temperature for 1 day, and placed in a high humidity and room temperature environment for curing for 27 days. After that, the compressive strength and tensile strength were tested. The test results are shown in Table 1.
[0063] Table 1 Compressive and tensile strength test results
[0064]
[0065]
[0066] As can be seen from Table 1, the ultimate strain of high-strength and high-toughness concrete prepared in Examples 1 to 3 is not less than 3%. At the same time, the compressive strength is not less than 60MPa, while the axial tension ultimate strain of Comparative Example 1 is only 2.5%. Thus, replacing PVA fibers with strip-shaped aragonite whiskers and hydrated calcium aluminate carbonate mixture can play a bridging effect. When concrete is subjected to tension, the extension of its crack width is limited, effectively improving its toughness. At the same time, carbon dioxide is absorbed by calcium hydroxide solution, which reduces the carbon emissions of the natural environment and is conducive to the advancement of environmentally friendly projects. In addition, hydrated calcium aluminate carbonate is generated from gold tailings and high-alumina cement, which improves the utilization value of gold tailings. As described above, the environmentally friendly carbon-reducing high-strength and high-toughness concrete provided by the present invention, which uses gold tailings to synthesize strip-shaped aragonite whiskers and hydrated calcium aluminate carbonate mixture instead of fibers, can be widely used in concrete slabs, beams and other components in engineering construction.
[0067] In order to verify the influence of different incorporation ratios of strip aragonite whiskers and hydrated calcium aluminate on high-strength and high-toughness concrete, high-strength and high-toughness concrete was cast with different incorporation ratios and the mechanical properties were tested.
[0068] Example 4
[0069] Embodiment 4 provides a method for preparing an environmentally friendly, carbon-reducing, high-strength, high-toughness concrete, comprising the following steps:
[0070] (1) Weigh 265 parts of cement, 265 parts of fly ash, 250 parts of silica fume, 250 parts of gold tailings sand, and 10 parts of thickener in a reactor and stir for 3 minutes to obtain a dry mix;
[0071] (2) Slowly add 20 parts of water reducer into 115 parts of water and stir for 5 minutes to obtain a uniform mixture;
[0072] (3) Weigh 50 parts of hydrated calcium aluminate, put it into the mixture and stir for 10 minutes until it is uniform, then place it in a high humidity and normal temperature environment, and after solidification, obtain an environmentally friendly, carbon-reducing, high-strength and high-toughness concrete material.
[0073] Example 5
[0074] Embodiment 5 provides a method for preparing an environmentally friendly, carbon-reducing, high-strength, high-toughness concrete, comprising the following steps:
[0075] (1) Weigh 265 parts of cement, 265 parts of fly ash, 250 parts of silica fume, 250 parts of gold tailings sand, and 10 parts of thickener in a reactor and stir for 3 minutes to obtain a dry mix;
[0076] (2) Slowly add 20 parts of water reducer into 115 parts of water and stir for 5 minutes to obtain a uniform mixture;
[0077] (3) Weigh 10 parts of aragonite whiskers and 40 parts of hydrated calcium aluminate, put them into the mixture and stir for 10 minutes until they are uniform, then place them in a high humidity and room temperature environment, and after solidification, obtain an environmentally friendly, carbon-reducing, high-strength, and high-toughness concrete material.
[0078] Example 6
[0079] Example 6 provides a method for preparing an environmentally friendly, carbon-reducing, high-strength, high-toughness concrete, comprising the following steps:
[0080] (1) Weigh 265 parts of cement, 265 parts of fly ash, 250 parts of silica fume, 250 parts of gold tailings sand, and 10 parts of thickener in a reactor and stir for 3 minutes to obtain a dry mix;
[0081] (2) Slowly add 20 parts of water reducer into 115 parts of water and stir for 5 minutes to obtain a uniform mixture;
[0082] (3) Weigh 20 parts of aragonite whiskers and 30 parts of hydrated calcium aluminate, put them into the mixture and stir for 10 minutes until they are uniform, then place them in a high humidity and room temperature environment, and after solidification, obtain an environmentally friendly, carbon-reducing, high-strength, and high-toughness concrete material.
[0083] Example 7
[0084] Example 7 provides a method for preparing an environmentally friendly, carbon-reducing, high-strength, high-toughness concrete, comprising the following steps:
[0085] (1) Weigh 265 parts of cement, 265 parts of fly ash, 250 parts of silica fume, 250 parts of gold tailings sand, and 10 parts of thickener in a reactor and stir for 3 minutes to obtain a dry mix;
[0086] (2) Slowly add 20 parts of water reducer into 115 parts of water and stir for 5 minutes to obtain a uniform mixture;
[0087] (3) Weigh 30 parts of aragonite whiskers and 20 parts of hydrated calcium aluminate, put them into the mixture and stir for 10 minutes until they are uniform, then place them in a high humidity and room temperature environment, and after solidification, obtain an environmentally friendly, carbon-reducing, high-strength, and high-toughness concrete material.
[0088] Example 8
[0089] Embodiment 8 provides a method for preparing an environmentally friendly, carbon-reducing, high-strength, high-toughness concrete, comprising the following steps:
[0090] (1) Weigh 265 parts of cement, 265 parts of fly ash, 250 parts of silica fume, 250 parts of gold tailings sand, and 10 parts of thickener in a reactor and stir for 3 minutes to obtain a dry mix;
[0091] (2) Slowly add 20 parts of water reducer into 115 parts of water and stir for 5 minutes to obtain a uniform mixture;
[0092] (3) Weigh 40 parts of aragonite whiskers and 10 parts of hydrated calcium aluminate, put them into the mixture and stir for 10 minutes until they are uniform, then place them in a high humidity and room temperature environment, and after solidification, obtain an environmentally friendly, carbon-reducing, high-strength, and high-toughness concrete material.
[0093] Example 9
[0094] Example 9 provides a method for preparing an environmentally friendly, carbon-reducing, high-strength, high-toughness concrete, comprising the following steps:
[0095] (1) Weigh 265 parts of cement, 265 parts of fly ash, 250 parts of silica fume, 250 parts of gold tailings sand, and 10 parts of thickener in a reactor and stir for 3 minutes to obtain a dry mix;
[0096] (2) Slowly add 20 parts of water reducer into 115 parts of water and stir for 5 minutes to obtain a uniform mixture;
[0097] (3) Weigh 50 parts of aragonite whiskers, put them into the mixture and stir for 10 minutes until it is uniform, then place it in a high humidity and room temperature environment, and after solidification, obtain an environmentally friendly, carbon-reducing, high-strength, and high-toughness concrete material.
[0098] The concrete materials prepared in Examples 4 to 9 were poured into a mold, cured at room temperature for 1 day, then demolded, placed in a high humidity and room temperature environment for 27 days, and then tested for compressive strength and tensile strength. The test results are shown in Table 2.
[0099] Table 2 Compressive and tensile strength test results
[0100]
[0101]
[0102] Comparing the test results of each group, it can be seen that the compressive strength of the group of 30 parts of aragonite whiskers and 20 parts of hydrated calcium aluminate carbon is the highest, which is 81.2MPa; the initial crack strength of axial tension is 5.7MPa. Therefore, the axial tensile ultimate strength of the group of 20 parts of aragonite whiskers and 30 parts of hydrated calcium aluminate carbon is the highest, which is 5.4MPa, and the maximum axial tensile ultimate strain is 3.6%.
[0103] It should be noted that, in this article, the terms "include", "comprises" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, an element defined by the sentence "comprises a ..." does not exclude the existence of other identical elements in the process, method, article or device including the element.
[0104] In addition, it should be noted that the scope of the methods and systems in the embodiments of the present invention is not limited to performing functions in the order shown or discussed, and may also include performing functions in a substantially simultaneous manner or in reverse order according to the functions involved. For example, the described methods may be performed in an order different from that described, and various steps may be added, omitted, or combined. In addition, features described with reference to certain examples may be combined in other examples.
[0105] The embodiments of the present invention are described above, but the present invention is not limited to the above-mentioned specific implementation modes. The above-mentioned specific implementation modes are merely illustrative and not restrictive. Under the guidance of the present invention, ordinary technicians in this field can also make many forms without departing from the scope of protection of the purpose of the present invention and the claims, all of which are protected by the present invention.
Claims
1. An environmentally friendly, carbon-reducing, high-strength, high-toughness concrete, characterized in that: Calculated by weight, it includes 265-310 parts of cement, 265-930 parts of fly ash, 50-250 parts of silica fume, 250 parts of gold tailings sand, 20-150 parts of water reducer, 10-20 parts of thickener, 30-50 parts of a mixture of hydrated calcium aluminate and strip aragonite whiskers, and 115-500 parts of water, wherein the water-to-cement ratio is 0.2-0.
35.
2. The environmentally friendly, carbon-reducing, high-strength, high-toughness concrete according to claim 1, characterized in that: The water reducing agent is selected from polycarboxylic acid series high efficiency water reducing agent, and the water reducing rate is greater than 20%.
3. The environmentally friendly, carbon-reducing, high-strength, high-toughness concrete according to claim 1 is characterized in that: The thickener is selected from hydroxypropyl cellulose thickener, and the viscosity is between 3500 and 4000 cpa·s.
4. The environmentally friendly, carbon-reducing, high-strength, high-toughness concrete according to claim 1, characterized in that: The mixture of hydrated calcium aluminate and long rod-shaped aragonite was prepared by the following method: The gold tailings are placed in a saturated solution of calcium hydroxide to provide crystallization sites for aragonite whiskers; Add magnesium chloride powder and high alumina cement and stir evenly until all are dissolved to form a mixed suspension of magnesium hydroxide and high alumina cement; The mixed suspension of magnesium hydroxide and high-alumina cement is heated to maintain the temperature of 80°C, and carbon dioxide gas is introduced. Under the action of magnesium ions, calcium ions react with carbon dioxide to form calcium carbonate precipitates and magnesium carbonate precipitates. Calcium carbonate uses gold tailings as nucleation points to form strip-shaped aragonite whiskers. The calcium carbonate component in the gold tailings reacts with high-alumina cement to form needle-shaped hydrated calcium aluminate. After a certain period of time, the mixture of strip-shaped aragonite whiskers and hydrated calcium aluminate is taken out.
5. The environmentally friendly, carbon-reducing, high-strength, high-toughness concrete according to claim 4 is characterized in that: After 5 hours, the mixture of strip-like aragonite whiskers and hydrated calcium aluminate carbon was taken out.
6. The environmentally friendly, carbon-reducing, high-strength, high-toughness concrete according to claim 1, characterized in that: In the mixture of hydrated calcium aluminate carbonate and strip-shaped aragonite whiskers, the ratio of hydrated calcium aluminate carbonate to strip-shaped aragonite whiskers is 1:0.25-4.
7. A method for preparing the environmentally friendly, carbon-reducing, high-strength, high-toughness concrete according to any one of claims 1 to 6, characterized in that: The steps include: Step 1: provide 265-310 parts of cement, 265-930 parts of fly ash, 50-250 parts of silica fume, 250 parts of gold tailings, 20-150 parts of water reducer, 10-20 parts of thickener, 30-50 parts of a mixture of hydrated calcium aluminate and long rod-shaped aragonite, and 115-500 parts of water, by weight; Step 2: Add cement, fly ash, silica fume, gold tailings sand and thickener into a reactor and stir evenly, then add water and water reducing agent and continue stirring to form a uniform mixture; Step three, adding hydrated calcium aluminate and strip-shaped aragonite whisker mixture to the mixture, stirring evenly, placing it in a high humidity and normal temperature environment, and obtaining an environmentally friendly, carbon-reducing, high-strength and high-toughness concrete material after solidification.
8. The preparation method according to claim 6, characterized in that: In step 2, the stirring time in the reactor is 3 minutes; the stirring time is continued for 5 minutes.
9. The preparation method according to claim 6, characterized in that: In step 3, the stirring time is 10 minutes.
Citation Information
Cited By
Low-shrinkage high-toughness concrete material as well as preparation method and application thereof
CN120058299A